(untitled) (Revista Apotheke, 2021)
John Dewey has made significant contributions to help us better understand the experience of being and expressing in the world. Based on his philosophy of education, this paper aims to present and discuss the idea of expressiveness as an act and object and why it differs from the impulsion or act of direct discharge and what is the role of the Deweyan experience in artistic expressiveness. In order to organize the ideas or concepts presented, the work was divided into topics in order to answer the following questions: What differentiates a impulsion or direct discharge of emotions of an expressive act? What is the relationship between experience and the expressive act? What about the possible difference between the act and the expressive object? What are the two types of responses in the expressive act and how do they work? And, what does it take for an object to be expressive?